2002
DOI: 10.1063/1.1532771
|View full text |Cite
|
Sign up to set email alerts
|

Graded ferroelectric thin films: Possible origin of the shift along the polarization axis

Abstract: Hysteresis measurements performed on graded Pt/lead zirconate titanate (PZT)/Pt structures with well oxygenated PZT films do not display any shift along the polarization axis (Voffset) as previously reported. On the other hand, when the PZT graded films were grown under low oxygen pressure, an offset voltage was measured. This shift was systematically enhanced after cycling the film as for fatigue measurements. It was also observed that the Voffset is independent of the value of the reference capacitor used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In agreement with the views of Poullain et al 29 and Bouregba et al, 30 electrical conductivity in the ferroelectric film material should have an important role to play. Previously, we have demonstrated the significance of conductivity to understand some interesting polarization switching results 37 and in the poling process of ferroelectric composites.…”
Section: B Polarization Offsets In Ferroelectrics With Asymmetric Cosupporting
confidence: 79%
See 1 more Smart Citation
“…In agreement with the views of Poullain et al 29 and Bouregba et al, 30 electrical conductivity in the ferroelectric film material should have an important role to play. Previously, we have demonstrated the significance of conductivity to understand some interesting polarization switching results 37 and in the poling process of ferroelectric composites.…”
Section: B Polarization Offsets In Ferroelectrics With Asymmetric Cosupporting
confidence: 79%
“…26 -28 On the other hand, the anomalous vertical offset of hysteresis loops observed in graded ferroelectric films ͑e.g., temperature or compositionally graded͒ was also suggested to be an effect of asymmetrical leakage current. 29 Recently, Bouregba et al demonstrated this idea by setting diodes and resistors in parallel with a nongraded structure. 30 Without considering the role of ferroelectric properties ͑in their theoretical analysis, the ferroelectric sample is treated as a series connection of a linear resistor and a diode͒, they obtained an expression for the dynamic behavior of polarization offset.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, approaches involving asymmetric conductivity have been applied to study the vertical shift observed in graded ferroelectrics. [16][17][18] This mechanism leading to asymmetric leakage current has long been observed and discussed in literature. [7][8][9]19,20 The accumulated interfacial charge will allow the buildup of an internal bias field to displace the hysteresis loop from the origin.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent results have shown the polarization offsets in graded PZT to be sensitive to the ambient oxygen concentration, giving rise to possible oxygen sensor applications. 5 Theoretical models have played key roles in providing deeper insight, and different approaches have been proposed. The offset has been interpreted as a static polarization developed across the ferroelectric film under the application of an alternating voltage.…”
Section: Introductionmentioning
confidence: 99%